Answer:
according to me 1st option seems to be correct❤️
Step-by-step explanation:
the answer is E
which 2
its easy bro
F(x) = 3x - 2
f(8) = 3(8) - 2
f(8) = 24 - 2
f(8) = 22
f(-5) = 3(-5) - 2
f(-5) = -15 - 2
f(-5) = -17
f(8) - f(-5) = 22 - (-17)
f(8) - f(-5) = 39
Hope this helped! Good luck! :)
Answer:
Your answer is 3.1
Step-by-step explanation:
Wherever you see j, substitute 5. Wherever you see k, substitute 3
1. Set up:
2. Multiply 4.7 * 5, to get 23.5
3. Multiply 6.8 * 3 to get 20.4
4. Subtract 23.5-20.4
5. Final anwer - 3.1
Hope this helps!